2023
DOI: 10.3389/fncel.2023.1115703
|View full text |Cite|
|
Sign up to set email alerts
|

Electrically-evoked responses for retinal prostheses are differentially altered depending on ganglion cell types in outer retinal neurodegeneration caused by Crb1 gene mutation

Abstract: BackgroundMicroelectronic prostheses for artificial vision stimulate neurons surviving outer retinal neurodegeneration such as retinitis pigmentosa (RP). Yet, the quality of prosthetic vision substantially varies across subjects, maybe due to different levels of retinal degeneration and/or distinct genotypes. Although the RP genotypes are remarkably diverse, prosthetic studies have primarily used retinal degeneration (rd) 1 and 10 mice, which both have Pde6b gene mutation. Here, we report the electric response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…Individualized electrical stimuli from the independent electrodes on MEAs can be used to target different types of cells, such as ON-and OFF-cells. Moreover, researchers found that the response to an electric pulse produced by RGCs is also dependent on the patient disease genotype [51]. Patients with varying genotypes of retinitis pigmentosa would, therefore, have varying quality of prosthetic vision, even though the same device may be implanted in all patients.…”
Section: Electric Stimulation Parameters For Selective Cell Activatio...mentioning
confidence: 99%
“…Individualized electrical stimuli from the independent electrodes on MEAs can be used to target different types of cells, such as ON-and OFF-cells. Moreover, researchers found that the response to an electric pulse produced by RGCs is also dependent on the patient disease genotype [51]. Patients with varying genotypes of retinitis pigmentosa would, therefore, have varying quality of prosthetic vision, even though the same device may be implanted in all patients.…”
Section: Electric Stimulation Parameters For Selective Cell Activatio...mentioning
confidence: 99%
“…9), each sublamina may be accurately targeted using the electrodes we simulated here, potentially improving the performance of retinal prostheses by more preferential activation of either ON or OFF pathway. However, it would be considerably challenging in the degenerate retinas in which the laminar structure is altered [68,69]. Along with previous efforts of stimulation parameter optimization for the enhanced selective activation [58,59,[63][64][65][66][67], the hardware approach such as the accurate positioning of penetrating electrodes may further advance discriminate activation of ON or OFF pathway.…”
Section: A Clinical Implications Of This Simulation Studymentioning
confidence: 99%
“…This limitation is expected to be easily overcome if reliable information becomes available, as our framework can readily accommodate anisotropic conductivities. Moreover, the retinal degeneration substantially alters not only RGC spiking patterns [68,70] but also anatomical structures of the retina [68,69], which is highly likely to change the spatial conductivity properties of the retina. Therefore, it is essential to precisely measure electrical conductivities of each retinal > REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 8 layers.…”
Section: B Limitation Of Our Studymentioning
confidence: 99%